Genomic epidemiology and resistome dynamics of Enterobacter species in a Portuguese Open Air Laboratory: the emergence of the FRI-8 carbapenemase - Pedro Teixeira; Miguel Ramos; Rani Rivière; Mónica Azevedo; Mónica Azevedo; Mónica Azevedo; Mário Ferreira; Maria Manuela Cano; Patrícia Vieira; Lígia Reis; Rui Matias; João Rodrigues; et al. (Frontiers in Microbiology)
Interconnected reservoirs contribute to the global spread of antimicrobial resistance (AMR), including carbapenem- and colistin-resistant Enterobacterales, highlighting the need for a One Health approach. We assessed the genomic epidemiology, diversity and AMR mechanisms of Enterobacter spp. across interconnected human, animal, plant, and environmental reservoirs in a Portuguese Open Air Laboratory. Over a one year monitoring period, samples from 12 different compartments were collected and processed using selective media to isolate Enterobacter spp., which were subjected to antibiotic susceptibility testing, whole-genome sequencing and subsequent analyses to identify AMR determinants, characterize plasmids and phylogenetic relationships. We established a collection of 61 Enterobacter isolates spanning nine species and 32 sequence types, including 16 novel ones, across nine compartments (river water, wastewater, soil, manure, feed, air, farmers, pigs, wild animals), reflecting the diversity and ubiquity of Enterobacter species. Core-genome analysis revealed eight genetic clusters, suggesting clonal transmission across compartments. In total, 29 antibiotic resistance genes were detected across all isolates. Notably, this is the first documentation of blaFRI-harbouring Enterobacterales in European environmental settings and the first to describe blaFRI, blaIMI and mcr-10 genes in Portugal. blaFRI-8 was detected in all E. vonholyi isolates (n = 17), located on four different IncFII(Yp) plasmids, and blaIMI-6 in an E. asburiae isolate, flanked by IS3 family transposases. E. vonholyi and the blaIMI-6-harbouring E. asburiae isolate were resistant to carbapenems. A mcr-10.1 gene was identified in an E. roggenkampii isolate on an IncFII(pECLA) plasmid. These plasmids exhibited high sequence similarity with global counterparts, indicating potential for horizontal gene transfer. Other antimicrobial resistance genes included qnrE1, sul1, and aadA2. Our findings underscore the importance of Enterobacter as vectors for AMR and the critical role of environmental compartments in its dissemination, reinforcing the importance of adopting a One Health approach to fully understand AMR dynamics.